P388 Evolution of hepatitis C care cascades among HIV and hepatitis B co-infected patients in british columbia, canada. (14th July 2019) - Mckee, Geoff; Chapinal, Nuria; Butt, Zahid; Rossi, Carmine; Wong, Stanley; Gilbert, Mark; Wong, Jason; Alvarez, Maria; Darvishian, Maryam; Bartlett, Sofia; Pearce, Margo; Samji, Hasina; et al.
Abstract : Background: Improvements in tolerability and cure rates of hepatitis C virus (HCV) with direct acting antiviral (DAA) treatment led to expansion of patients treated for HCV; however, research examining the impact of these changes on linkage to care and treatment initiation among patients with hepatitis B (HBV) and HIV co-infection is limited. We compared the care cascades for patients with HBV and HIV co-infection before and after the introduction of DAAs, among a large population-based cohort in British Columbia (BC). Methods: We analyzed data from the BC Hepatitis Testers Cohort, including all individuals tested for HCV or HIV between 1992 and 2015 at the BC Centre for Disease Control Public Health Laboratory, as well as cases of HIV (1980–2015), HCV (1990–2015), HBV (1990–2015), and active tuberculosis (1990–2015) included in registries of reportable diseases in BC. Care cascades were stratified by HIV and HBV co-infection and compared for all individuals with HCV alive at the end of 2012 (pre-DAA) and 2017 (post-DAA), including the following stages: (1) HCV diagnosed; (2) HCV RNA tested; (3) HCV RNA positive; (4) HCV genotyped; (5) initiated antiviral treatment; and (6) sustained viral response (SVR). Results: 53, 030 individuals diagnosed with HCV were alivein 2012 and 52, 987 in 2017, were included in respective care cascades. In comparison to the pre-DAA era (2012), there were considerable increases in genotyping, treatment, and cure among individuals from all co-infection categories in 2017. For example, the proportion of those with known active infection who initiated treatment was 52% versus 23% among HCV/HIV (p<0.01), 51% versus 33% among HCV/HBV (p<0.01), 54% versus 20% among HCV/HBV/HIV (p<0.01), in 2017 and 2012 respectively. Conclusion: Considerable improvements have been noted in linkage to care and treatment of HCV in BC following introduction of DAAs, particularly among patients with HBV and HIV co-infections. Disclosure: No significant relationships.